The Relationship Between Curriculum Literacy with Teacher's Job Satisfaction and The Sense of Self-Worth in Secondary Schools - Nazaree Nia, Marzieh (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to explore the relationship between curriculum literacy and its impact on teachers' job satisfaction and sense of self-worth in secondary schools in Tehran.Methodology: A descriptive-correlational, cross-sectional study design was employed, utilizing a sample of 250 secondary school teachers in Tehran, selected through a two-stage cluster sampling method. Data were collected using three validated questionnaires measuring curriculum literacy, job satisfaction, and self-worth. Statistical analyses included Pearson correlation to examine the relationships between the variables and linear regression to assess the predictive power of curriculum literacy on job satisfaction and self-worth, with SPSS software utilized for all analyses.Findings: The results revealed statistically significant positive correlations between curriculum literacy and both job satisfaction (r = 0.220, p < 0.01) and self-worth (r = 0.223, p < 0.01). Regression analysis indicated that curriculum literacy significantly predicts job satisfaction (B = 0.350, p < 0.01) and self-worth (B = 0.327, p < 0.01), with standard coefficients suggesting a moderate effect size. These findings underscore the importance of curriculum literacy as a contributor to teachers' job satisfaction and self-worth.Conclusion: The study concludes that curriculum literacy plays a significant role in enhancing teachers' job satisfaction and sense of self-worth in the context of Tehran's secondary schools. These results highlight the need for educational policies and professional development programs focused on improving teachers' curriculum literacy. Such initiatives could contribute to creating a more satisfying and rewarding teaching environment, ultimately benefiting educational outcomes.